Analgesic Prescription Patterns and Pain Outcomes in Southeast Asia: Findings From the Analgesic Treatment of Cancer Pain in Southeast Asia Study - Thinh, Dang Huy Quoc; Sriraj, Wimonrat; Mansor, Marzida; Tan, Kian Hian; Irawan, Cosphiadi; Kurnianda, Johan; Nguyen, Yen Phi; Ong-Cornel, Annielyn; Hadjiat, Yacine; Moon, Hanlim; Javier, Francis O. (American Society of Clinical Oncology, 2018)
Purpose :To identify patterns of analgesic prescription and to explore patient-reported pain intensity, sleep disturbance, and quality of life among cancer patients with pain in Southeast Asia (SEA). Methods: This cross-sectional observational study included 465 adult outpatients prescribed analgesics for cancer pain for 1 month or longer at 22 sites in Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. Data on analgesic prescription and cancer characteristics were extracted from medical records. Pain intensity, sleep disturbance, and quality of life measures were recorded via questionnaires. Results: Most patients (84.4%) had stage III or IV cancer. A total of 419 patients (90.7%) were prescribed opioids; of these, 42.2% received only weak opioids, whereas 57.8% received at least one strong opioid. The mean worst pain intensity during the past 24 hours was 4.76 (standard deviation [SD], 2.47) on a scale of 0 (no pain) to 10 (worst possible pain); the mean current pain intensity was 4.10 (SD, 2.61). More than half of patients (54.8%) reported sleep disturbance caused by pain in the past 7 days. The majority of patients reported problems with pain/discomfort (82.3%), usual activities (65.8%), mobility (58.2%), and anxiety/depression (56.3%). The median daily dose prescribed in oral morphine equivalents was 30 mg for both morphine and tramadol. Conclusion: Despite unrelieved pain, sleep disturbance, and issues with quality of life, a notable proportion of patients were prescribed only weak opioids, and opioid doses prescribed were generally low. Efforts focused on encouragement of prescriptions with analgesic strength and/or doses proportional to the pain management needs of patients are vital to improve the status of cancer pain management in the region.